Profile of drug administration errors in anesthesia among anesthesiologists from Santa Catarina - Thomas Rolf Erdmann; Jorge Hamilton Soares Garcia; Marcos Lázaro Loureiro; Marcelo Petruccelli Monteiro; Guilherme Muriano Brunharo (Brazilian Journal of Anesthesiology, 2016)
Introduction: Anesthesiology is the only medical specialty that prescribes, dilutes, and administers drugs without conferral by another professional. Adding to the high frequency of drug administration, a propitious scenario to errors is created. Objective: Access the prevalence of drug administration errors during anesthesia among anesthesiologists from Santa Catarina, the circumstances in which they occurred, and possible associated factors. Materials and methods: An electronic questionnaire was sent to all anesthesiologists from Sociedade de Anestesiologia do Estado de Santa Catarina, with direct or multiple choice questions on responder demographics and anesthesia practice profile; prevalence of errors, type and consequence of error; and factors that may have contributed to the errors. Results: Of the respondents, 91.8% reported they had committed administration errors, adding the total error of 274 and mean of 4.7 (6.9) errors per respondent. The most common error was replacement (68.4%), followed by dose error (49.1%), and omission (35%). Only 7% of respondents reported neuraxial administration error. Regarding circumstances of errors, they mainly occurred in the morning (32.7%), in anesthesia maintenance (49%), with 47.8% without harm to the patient and 1.75% with the highest morbidity and irreversible damage, and 87.3% of cases with immediate identification. As for possible contributing factors, the most frequent were distraction and fatigue (64.9%) and misreading of labels, ampoules, or syringes (54.4%). Conclusion: Most respondents committed more than one error in anesthesia administration, mainly justified as a distraction or fatigue, and of low gravity. Resumo: Introdução: A anestesiologia é a única especialidade médica que prescreve, dilui e administra os fármacos sem conferência de outro profissional. Somando-se a alta frequência de administração de fármacos, cria-se o cenário propício aos erros. Objetivo: Verificar a prevalência dos erros de administração de medicamentos durante anestesia, entre anestesiologistas catarinenses, as circunstâncias em que ocorreram e possíveis fatores associados. Materiais e métodos: Um questionário eletrônico foi enviado a todos os anestesiologistas da Sociedade de Anestesiologia do Estado de Santa Catarina contendo respostas diretas ou de múltipla escolha sobre dados demográficos e perfil da prática anestésica do entrevistado; prevalência de erros, tipo e consequência do erro; e fatores que possivelmente contribuíram para os erros. Resultados: Dos entrevistados, 91,8% afirmaram ter cometido erro de administração, somando total de erros de 274 e média de 4,7 (6,9) erros por entrevistado. O erro mais comum foi substituição (68,4%), seguido por erro de dose (49,1%) e omissão (35%). Apenas 7% dos entrevistados referiram erros de administração no neuroeixo. Quanto às circunstâncias dos erros, ocorreram principalmente no período matutino (32,7%), na manutenção da anestesia (49%), com 47,8% sem danos ao paciente e 1,75% com maior morbidade com dano irreversível e em 87,3% dos casos a identificação imediata. Quanto aos possíveis fatores contribuintes, os mais frequentes foram: distração e fadiga (64,9%) e leitura errada dos rótulos de ampolas ou seringas (54,4%). Conclusão: A maioria dos anestesiologistas entrevistados cometeu mais de um erro de administração em anestesia, principalmente justificado como distração ou fadiga, de baixa gravidade. Keywords: Medical errors, Drug errors, Anesthesiology, Anesthesia, Palavras-chave: Erros médicos, Erros de medicação, Anestesiologia, Anestesia